1992
DOI: 10.1093/oxfordjournals.annonc.a058255
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of chemotherapy versus chemotherapy plus radiotherapy for stage III-IV A &B Hodgkin's disease

Abstract: A total of 151 patients with previously untreated Hodgkin's disease, clinical stages III-IV A & B, were randomized to receive CVPP for 6 cycles, or CVPP plus RT 3000 cGy to previously involved areas between the 3rd and 4th cycles. CVPP consists of cyclophosphamide 600 mg/m2/i.v., vinblastine 6 mg/m2/i.v. on day 1, procarbazine 100 mg/m2/p.o. and prednisone 40 mg/m2/p.o. on days 1 to 14. Both groups displayed similar clinical characteristics at diagnosis. Sixty-six were treated with CVPP + RT (52 St III and 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…[5][6][7][8]18,[21][22][23][24][25][26] [27] and may be associated with higher rates of late-term side effects, such as secondary malignancies. [28] The relative infrequent use of RT at academic/research programs, demonstrated in this study, may be explained by greater access and comfort with salvage programs such as ASCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8]18,[21][22][23][24][25][26] [27] and may be associated with higher rates of late-term side effects, such as secondary malignancies. [28] The relative infrequent use of RT at academic/research programs, demonstrated in this study, may be explained by greater access and comfort with salvage programs such as ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Studies have found the relative risk of death from cardiovascular disease persists >20 years after treatment and is related to RT doses >3,000cGy, supra-diaphragmatic fields, and exposure to anthracycline/alklyating agents. 24,26 With effective chemotherapy regimens, modern RT field reductions now only include the involved site and treatment to much lower doses. [1,2,4,30,31] This study reflects a time period in which STLI and EFRT was no longer standard practice and the movement toward IFRT/ISRT [32] Field reduction to the "involved-node" has been estimated to reduce 25-year absolute excess risk of cardiac events by 5.1% when compared to traditional mantle fields.…”
Section: Discussionmentioning
confidence: 99%
“…The role of consolidative RT after intense CTX for patients in advanced stages is discussed controversially. Results of randomized trials challenged the benefit of adjuvant RT (4)(5)(6)(7)(8)(9), and therefore the European Organization for Research and Treatment of Cancer (EORTC) conducted a trial to determine the role of consolidative RT after CTX. The data of this analysis showed no improvement in outcome when adding consolidative involved-field RT (IF-RT) for patients in complete remission after CTX (10).…”
Section: Introductionmentioning
confidence: 99%
“…and the United States have been unable to clearly show improved disease-free or overall survival with additional radiotherapy (67,74). A randomized study from Argentina reported better disease-free survival, although no difference in overall survival, with combination therapy than with chemotherapy (75). However, optimum chemotherapy was not used, and unusually high recurrence was noted in the irradiated areas.…”
Section: Advanced Disease: Stage Iiib-ivmentioning
confidence: 99%